Cognitive, affective, and social drivers of music fan-related behavior - Ganhão, M.; Loureiro, S. M. C.; Guerreiro, J.; Bilro, R.G.; Rodrigues, M. B. (Marketing in a multicultural and vibrant world: Proceedings for the 2024 AMS World Marketing Congress, 2024)
The music industry underwent a digital revolution, culminating in the dominance of streaming services. These services transformed music consumption habits, providing constant access to music and an abundance of options. However, understanding what drives music consumers’ loyalty to their favorite artists in this vast landscape remains a critical question. With both popular and lesser-known artists now sharing the same platforms, fostering loyalty has become a challenge. Surprisingly, there is limited research on brand loyalty toward music artists. To address this gap, our study investigates the factors influencing attitude and fan-related behavior. Data collection and analysis were conducted through quantitative methods using an online questionnaire based on relevant literature on the topic. Findings reveal that Brand Coolness, Perceived Sense of Brand Community, Perceived Quality, and Perceived Social value predict attitudes toward music artists, which subsequently influences behavioral loyalty. Finally, this study evidences the need for musicians and managers to invest in amplifying loyalty from the fans, through these predictors.